Riesgos ambientales del faenamiento de aves en las avícolas. distrito Iquitos, loreto – 2023 - Moreto Bautista, Jefferson Paolo (2024)
The thesis was carried out around the poultry farms of the Belén market in the city of Iquitos in order to evaluate the environmental risks associated with the slaughtering process of birds in poultry farms. It is a quantitative research of the observational, descriptive, analytical, cross-sectional type. The primary information was obtained through the application of a structured interview with a reliability, Cronbach's alpha 0.815. For the correlation analysis between the indicators, the Rho Spearman correlation analysis was used. Obtaining the following. There is a tendency to increase slaughter volumes, due to the sustained increase in chicken consumption in the city. They make efficient use through recirculation systems to reduce their consumption, identifying that cleaning, disinfection and maintenance tasks are those that use the greatest amount of water. They recognize that they generate different types of solid waste such as feathers, blood waste, viscera among others, which are easily decomposed and highly polluting and that they manage it through the municipal waste collection service. They consider it important to reduce liquid waste with traces of blood, through appropriate practices in the slaughter of birds. Energy consumption increases as the level of production increases and therefore, they identify the need to make more efficient energy use. They recognize the importance of using various chemical substances in cleaning and disinfection tasks to improve health and hygiene and food safety, so they encourage the use of safe or harmless chemical products in the poultry industry. The correlation analysis between the amount of processed birds and the use of water, waste generation, energy use and the use of chemical substances does not have statistical significance, therefore, inefficient use of resources, energy and chemical products is not being generated in the slaughter of birds, so the alternative hypothesis is rejected and the null hypothesis is accepted.